Metode Bermain Peran sebagai Media Edukasi Komunikatif: Transformasi Pembelajaran Anak Usia Dini di Kawasan Terpencil - Nivaan, Varadilla Meiske Josefa; Afdhal, Afdhal (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
This study explores the effectiveness of the role play method as a communicative educational tool to enhance early childhood learning in remote areas, focusing on TK Ilwiaru Watumera Wakarleli, Maluku Barat Daya. Employing a qualitative approach, the research utilized observation, interviews, and documentation to assess the process and impact of role play-based learning on children’s interpersonal communication development. Findings indicate that the role play method significantly improves key aspects such as openness, empathy, supportive behavior, positive attitudes, and equality among children. Initially passive children became more active in both verbal and non-verbal communication, demonstrated increased social awareness, and were able to express themselves more confidently, including in family settings. The novelty of this study lies in its application of role play in early childhood education within remote communities, which typically lack access to modern pedagogical approaches. The study recommends the integration of role play-based teacher training to foster character development, strengthen interpersonal communication, and create an engaging and participatory learning environment. These findings contribute to the advancement of social sciences and humanities in the field of early childhood education.